Secondhand tobacco smoke in public venues in three Indonesian cities (Medical Journal of Indonesia, 2013)
Background: The aim of this study was to measure secondhand tobacco (including kretek) smoke (SHS) concentrations in public places in Jakarta, Bogor, and Palembang before laws banning smoking in public spaces went into effect. Methods: Particulate matter (PM2.5) was measured in 15 hospitals, 15 government offices, 30 restaurants, and 26 entertainment venues throughout the three cities. Also, in Jakarta, vapor-phase nicotine was measured in 5 schools, 5 hospitals, 5 government offices, 9 restaurants, and 10 entertainment venues. Data were analyzed descriptively. Differences by city and venue characteristics were analyzed by Studentâs t-test, ANOVA, and Bonferroni pairwise statistical tests. Results: Geometric mean PM2.5 levels were highest in entertainment venues (96 µg/m3), followed by restaurants (78 µg/m3), government offices (57 µg/m3), and hospitals (46 µg/m3). Air nicotine levels in Jakarta were highest in designated smoking areas (4.71 µg/m3) and designated non-smoking areas (1.55 µg/m3) of entertainment venues. These were followed by government offices (0.30 µg/m3), designated smoking areas (0.24 µg/m3) and designated non-smoking areas (0.19 µg/m3) of restaurants, hospitals (0.01 µg/m3), and schools (0.01 µg/m3). Conclusion: SHS was detected in all venues in the three cities in Indonesia. High levels of air nicotine were found in non-smoking areas of restaurants and entertainment venues, indicating that designated smoking areas are not an effective solution to eliminate SHS. There is no safe level of SHS exposure and thus SHS in these venues increases the risk of adverse health effects among children and adults. These findings support the need for 100% smoke-free laws covering all public venues in these and other Indonesian cities. (Med J Indones. 2013;22:232-7. doi: 10.13181/mji.v22i4.606)